L'oppidum de Saint-Blaise du Ve au VIIe s. (Bouches-du-Rhône) - Démians d'Archimbaud, Gabrielle (Documents d'archéologie française, 1994)
This volume presents important results not only for archaeology in Provence but also increases our knowledge of the Mediterranean world at the very begining of the Middle Ages. The recent excavations of Saint-Blaise oppidum, near the Rhône delta, have brought to light the different stages of the reoccupation, from the 5th to the 7th century, of this protohistoric site. The ceramic assemblage testifies the importance of trade: red slip wares, amphorae, grey coarse wares from North Africa, the eastern Mediterranean and Liguria, regional slip wares (DS.P.), etc. The discovery of glass-ware with christian motifs and of vitrified crucibles indicates the existence of glass-working; stone, bone and metal objects, the coins, the fauna, especially the abundant remains of shellfish consumed, enrich the image of the life on this oppidum, one of the most important in Provence during this period of crisis and of change.